2007
DOI: 10.1016/j.margeo.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Sr/Ca and Mg/Ca ratios in Niger Delta sediments: Implications for authigenic carbonate genesis in cold seep environments

Abstract: We report on a reconnaissance analysis of the geochemical composition of authigenic carbonates and sediment samples collected from various seepage sites on the Niger deep-sea fan. Our aim has been to investigate whether evidence for the presence of authigenic carbonates and gas hydrates within sediments is discernible from solid-phase sediment geochemistry. We show that sedimentary Sr/Ca and Mg/Ca ratios can be used to infer the presence of authigenic aragonite (Sr-rich) and Mg-rich carbonate phases (high-Mg c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
109
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(117 citation statements)
references
References 29 publications
8
109
0
Order By: Relevance
“…Occurrence of this CaCO 3 form could imply an increased water supply, as melt water from surrounding glaciers, or as runoff from higher precipitation, leading to dilution of the other minerals (Müller et al 1972). Alternatively, as proposed by Bayon et al (2007), low-Mg calcite may be of biogenic origin, formed by infaunal organisms such as ostracodes, which are abundant during this interval. Aquatic (nC 21 ) n-alkanes show the most depleted dD values in this unit, with a mean of -262% (Fig.…”
Section: Mineral Compositionmentioning
confidence: 90%
“…Occurrence of this CaCO 3 form could imply an increased water supply, as melt water from surrounding glaciers, or as runoff from higher precipitation, leading to dilution of the other minerals (Müller et al 1972). Alternatively, as proposed by Bayon et al (2007), low-Mg calcite may be of biogenic origin, formed by infaunal organisms such as ostracodes, which are abundant during this interval. Aquatic (nC 21 ) n-alkanes show the most depleted dD values in this unit, with a mean of -262% (Fig.…”
Section: Mineral Compositionmentioning
confidence: 90%
“…5e, and Sr/Ca, Fig. 5f) commonly used in the literature to trace terrestrial sources in marine environments (Schnetger et al, 2000;Bayon et al, 2007). Elements present in detrital silicate minerals such as Fe, Ti or Al showed increased values synchronous to the Ca peak (Fig.…”
Section: Gulf Of Lionmentioning
confidence: 94%
“…Aragonite cement formed at methane seeps in the Black Sea exhibits Sr contents as high as 9500 ppm, the associ− ated high−Mg−calcite revealed values of approximately 1200 ppm (Peckmann et al 2001). Similarly, aragonite cement of seep carbonates from the Niger Delta showed Sr contents of up to 12 000 ppm, much higher than the contents of 100 ppm to 1000 ppm found for other carbonate mineralogies including calcite and dolomite (Bayon et al 2007). Savard et al (1996) reported as much as 11 000 ppm Sr in aragonite cement of Cre− taceous seep limestone rocks.…”
mentioning
confidence: 90%